Usefulness of zebrafish in evaluating drug-induced teratogenicity in cardiovascular system. (2nd November 2019) - Watanabe, Ryo; Nakanishi, Yuki; Nijoukubo, Daisuke; Teraoka, Hiroki; Ogasawara, Hiroyuki; Mori, Kazuhiko
Abstract: To confirm the usefulness of zebrafish for evaluating the teratogenic potential of drug candidates, the effect of O -ethylhydroxylamine hydrochloride (OHY), which induces mutagenesis by methylation, was evaluated in teratogenicity studies in rats and zebrafish. In the rat teratogenicity study, OHY-induced cardiovascular malformations such as increased abnormal vascular structures and ventricular septal defects. In the teratogenicity study using zebrafish-injected microspheres and green fluorescent protein-expressing Tg zebrafish (flk1:EGFP), OHY exposure was associated with the loss or malformation of the mandibular arch, opercular artery, and fourth branchial arch. These results suggested that OHY-induced external malformations in zebrafish eleutheroembryos adequately reflect OHY's teratogenicity in rat fetuses. Moreover, the zebrafish teratogenicity study incorporating vascular morphological examinations, including those of blood vessels in the heart, head and trunk, is an easy and reliable screening method to detect potential drug-induced teratogenicity and phenotypic characteristics.